Motivational Dialogue in the Second Language Setting - James P. Lantolf (Cranmore Publishing, 2021)
This study argues for the relevance of a model of social interaction referred to as "motivational dialogue" as proposed by Patyayeva (2012) grounded in the concept of dialogue as proposed by L. S. Vygotsky and M. Bakhtin. The model accounts for two types of motivational dialogue: that which unfolds in social environments between two or more individuals and that which unfolds internally as private or inner speech. In the extension of Patyayeva's model to L2 teaching and learning situations, as proposed in the present study, two critical concepts of Vygotsky's theory are also brought into consideration: perezhivanie (the dialectical interaction between emotion and intellect) and the social situation of development (how a particular context is refracted through the personality of an individual who participates in that context. Two examples from the published literature (Matusov 2011) and Lantolf and Genung (2002) are used to illustrate how motivational dialogue might operate in educational settings. The study concludes with several recommendations for how future research might be carried out in L2 settings.